The essentials of instructional design: connecting fundamental principles with process and practice - Brown, Abbie H.; Green, Timothy D. (New York: Routledge, 2016)
This book is designed to introduce you to the foundational elements of instructional design - the fundamental principles, processes, and practices that currently shape and define the field. By not subscribing to any single ID model or approach, the authors are able to clearly articulate the principles of design (e.g. task analysis), and then they describe, compare, and contrast the processes of applying each principle as established by leaders in the field. Practical examples and application questions are woven throughout each chapter and present opportunities for you to check your understanding and apply what you've learned.
Keywords: Instructional Systems Design